Green spaces and adverse pregnancy outcomes. Issue 8 (23rd April 2014) - Agay-Shay, Keren; Peled, Ammatzia; Crespo, Antonia Valentín; Peretz, Chava; Amitai, Yona; Linn, Shai; Friger, Michael; Nieuwenhuijsen, Mark J
Abstract : Objective: The objective of this study was to evaluate the associations between proximity to green spaces and surrounding greenness and pregnancy outcomes, such as birth weight, low birth weight (LBW), very LBW (VLBW), gestational age, preterm deliveries (PTD) and very PTD (VPTD). Methods: This study was based on 39 132 singleton live births from a registry birth cohort in Tel Aviv, Israel, during 2000–2006. Surrounding greenness was defined as the average of satellite-based Normalised Difference Vegetation Index (NDVI) in 250 m buffers and proximity to major green spaces was defined as residence within a buffer of 300 m from boundaries of a major green space (5000 m 2 ), based on data constructed from OpenStreetMap. Linear regression (for birth weight and gestational age) and logistic regressions models (for LBW, VLBW, PTD and VPTD) were used with adjustment for relevant covariates. Results: An increase in 1 interquartile range greenness was associated with a statistically significant increase in birth weight (19.2 g 95% CI 13.3 to 25.1) and decreased risk of LBW (OR 0.84, 95% CI 0.78 to 0.90). Results for VLBW were in the same direction but were not statistically significant. In general, no associations were found for gestational age, PTD and VPTD. The findings were consistent with different buffer and green space sizes and stronger associations were observed among those of lower socioeconomic status. Conclusions: This study confirms the results of a few previous studies demonstrating an association between maternal proximity to green spaces and birth weight. Further investigation is needed into the associations with VLBW and VPTD, which has never been studied before.